THE DEVELOPMENT OF GUIDED INQUIRY SCIENCE LEARNING MATERIALS TO IMPROVE SCIENCE LITERACY SKILL OF PROSPECTIVE MI TEACHERS (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2016)
This study aimed to produce valid, practical and effective guided inquiry model science learning materials to enhance science literacy skill of prospective MI teachers. The tryout of the materials was implementedto students of MI teacher educationof Unipdu Jombang at academic year of 2015/2016 semesters 3 using One Group Pretest Posttest Design. The data collections were done using observation, testing, and questionnaires. Data were analysed using descriptive analysis of quantitative, qualitative and non-parametric statistical tests. The findings of the research were: 1) the learning materials were valid; 2) Practicality of the materials was tested through the implementation of lesson plans, while the learners’ activity wereappropriate to the guided inquirymodel; and 3) The effectiveness of the learning materials in terms of improvement of learning outcomes of students was seen from the n-gain with high category and increasing mastery of science literacy skills of learners also scored n-gain with high category and the response of students to the device and the implementation of learning is very positive. It was concluded that the materials were valid, practical, and effective to enhance science literacy skills of prospective MI teachers.